Directed motivational currents as a framework for mutual-benefit peer teaching in foreign language education - Ma, Shengnan (Frontiers in Psychology, 2025)
This study applies the Directed Motivational Currents (DMCs) framework to a mutual-benefit and student-led foreign language teaching model at a Chinese university. Eight language majors volunteered as peer instructors and 60 undergraduates enrolled as beginners of French, Japanese, Korean, or German. Drawing on the four DMCs dimensions (vision-based goals, triggering factors, facilitative structure, positive emotionality), the program offered weekly classes supported by quizzes, homework, and participation evaluations. Data from pre- and post-course questionnaires, classroom assessments, and semi-structured interviews were analyzed using a mixed-methods approach. Quantitative results showed that most learners were driven by intrinsic interest, maintained participation, and improved their quiz performance over the semester. Qualitative themes highlighted vivid learner and teacher visions, diverse triggers, supportive routines, and positive emotions for both groups. Overall, the findings suggest that a DMCs-informed peer-teaching model is a feasible non-profit approach for sustaining motivation and expanding equitable access to foreign language learning in higher education.